Optimising the national strategy for progressive employment absorption to ensure the rights and responsibilities of citizens in Indonesia - Ardyati, Rizda; Ikrimah, Afridah (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
<!-- ####### THIS IS A COMMENT - Visible only in the source editor #########--> Indonesia is experiencing a demographic transition phenomenon. This can be seen from the results of the 2010 population census, which showed a positive trend in the productive age population, namely 15-64 years. In that year, the proportion reached 66% of the total population. The potential growth of Indonesia's productive population can be an engine of sustainable economic growth or a source of social conflict between classes in the future, if the government cannot handle this potential, it will become a problem related to fulfilling the rights of citizens to get decent work, because instead of being absorbed into the workforce, it will cause social conflict. The data used for this research is secondary data obtained from library materials such as books, journals, and data from the Central Statistics Agency (BPS). The data used is a combined panel of time series and cross-sections from 2019 to 2023. The Human Development Index (HDI) of Central Java Province is still below the value of the HDI; this results in the HDI not having a significant effect on employment in the City / Regency in Central Java Province. This is because the human resources in the cities/districts of Central Java Province are still of low quality and unable to keep up with other provinces in Indonesia. The strategy that can be used in the framework of labour absorption is to improve resources to be more qualified so that they can get a job according to the business field they are interested in.